Left ventricular myocardial cellular perfusion against the background of cardiac contractility modulation in patients with heart failure and atrial fibrillation - V. A. Amanatova; A. A. Safiullina; T. M. Uskach; A. A. Ansheles; S. N. Tereshchenko; V. B. Sergienko (Российский кардиологический журнал, 2021)
Aim. To assess the effect of cardiac contractility modulation (CCM) in patients with heart failure (HF) and atrial fibrillation (AF) on left ventricular (LV) myocardial cellular perfusion using perfusion single photon emission computed tomography (SPECT).Material and methods. 99mTc-MIBI SPECT gated myocardial perfusion imaging was performed in 60 patients with HF and AF before implantation of CCM device and after 6-months follow-up. All patients received long-term optimal medication therapy for HF. Results. The results obtained indicate a significant positive effect of CCM use in patients with HF and AF on LV ejection fraction (increase from 22 [18;30] to 25,5 [19;38] (p=0,002)), LV volume (decrease in LV end-systolic volume from 187 [114;238] to 154 [100;201] (p=0,001), end-diastolic volume from 229 [174;290] to 209 [159;259] (p=0,007)), as well as myocardial perfusion values. There is a favorable myocardial perfusion dynamics, which was more pronounced in nonischemic HF: increase in SRS from 6 [5;9] to 8,0 [6;11] after 6 months (p=0,01)). The extent of impaired perfusion significantly decreases from 12 [9;17] to 9 [6;16] (p=0,04). An indicator reflecting the total impairment of LV myocardial perfusion significantly decreases: total perfusion deficit decreased from 10 [8;14] to 7 [6;14] after 6 months (p=0,02), compared with ischemia-related HF.Conclusion. Perfusion SPECT makes it possible to assess the myocardial cellular perfusion during CCM therapy in patients with HF of various origin and AF. CCM therapy improves myocardial contractility and perfusion in patients with HF and AF.